Model Teoritik Prestasi Akademik Mahasantri Ma’had Al Jamiah UIN Sayyid Ali Rahmatullah Tulungagung - Muhammad Sholihuddin Zuhdi; Ahmad Fauzan; Umi Aisyah (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2025)
Mahasantri have heavier study demands than students who only attend lectures because Mahasantri must participate in activities at the dormitory and on campus. The purpose of this study is to develop and test a theoretical model of academic achievement for Mahasantri at Ma'had al-Jami'ah UIN Sayyid Ali Rahmatullah Tulungagung, which involves three main psychological constructs: self-regulation, self-esteem, and achievement motivation. This study employs a quantitative approach using a theoretical model development research design, followed by statistical testing using Structural Equation Modeling (SEM). The study involved a sample size of 180 Mahasantri, who were deemed suitable and met the criteria for SEM analysis using the Maximum Likelihood method. The results of this study successfully developed a theoretical model explaining that academic achievement (PA) of Mahasantri is significantly influenced by self-esteem (HD), self-regulation (RD), and achievement motivation (MB) of Mahasantri.